Body parameters with application of optimal differential variation method in super cavity model - Ha, Tran Thu; Son, Nguyen Anh; Hai, Duong Ngoc (Vietnam Journal of Mechanics, 2016)
When a slender body moves very fast through water at sufficient speed the cavity phenomena is happened. In a cavity model the body’s lengths and cavitator diameter are determined by the differential variationoptimal method so that the velocity of body is maximum.